Implementasi Agile Scrum Pada Pengembangan Website untuk Manajemen Barang PT Alita Praya Mitra - Yusup Miftahuddin; Andika Wahyu Syaputra; Rifqi Fachriza Sukmana; Nurochman Rizky Apriadi; Rafli Adytia Nugraha; Rayhan Maulana Herdiansyah; Muhamad Rifki Pratama (Politeknik Negeri Cilacap, 2026)
PT Alita Praya Mitra is a company engaged in the field of Information and Communication Technology (ICT). In the process of managing Bill of Quantity (BoQ) data, the company does not yet have an integrated system, and data processing is still carried out conventionally, which requires a considerable amount of time. This condition causes the processes of recording, processing, and retrieving data to be less efficient and potentially prone to errors. Therefore, one possible solution is the development of an integrated web-based inventory management system. The system was developed using the Agile Scrum methodology, which consists of several stages, including user stories, product backlog, sprint planning, sprint backlog, and daily scrum. This method was chosen because it supports gradual and flexible system development based on user needs. Based on the testing results, the system has been successfully implemented and named the PO Management Tools. The implementation results show that the system can accelerate the BoQ data processing process and improve work efficiency. In addition, Agile Scrum has proven to support system development effectively even with a small development team.